Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Nibras Hijab Di Tangerang Selatan - Rahmawati, Sari; Sulistiani, Sinta (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the effect of promotion and price on purchasing decisions of Nibras Hijab consumers in South Tangerang both partially and simultaneously. This study uses a data collection method with a sampling technique of 97 respondents. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, regression, correlation coefficient analysis, determination coefficients, and hypothesis tests. The results show that price (X1) has a significant effect on purchasing decisions, with a regression equation of Y = 2.180 + 0.892X1. The correlation coefficient value is 0.756 The determination value is 57.2%. The hypothesis test shows t count> t table (11.270> 1.660). Promotion (X2) also has a significant effect on purchasing decisions with a regression equation of Y = 7.811 + 0.754X2. The correlation coefficient value is 0.705 The determination value is 49.7%. Hypothesis test shows t count > t table (9.690 > 1.660), price (X1) and promotion (X2) have a significant effect on purchasing decisions with the regression equation Y = 0.522 + 0.612X1 + 0.344X2. The correlation coefficient value is 0.619 and the determination value is 61.9%, and the hypothesis test shows F count > F table (76.295 > 3.093). Keywords: price,promotion, purchase decision